A solution for unregistered waqf land in Selangor / Nor Anisah Mohd Bakri - Mohd Bakri, Nor Anisah (Academy of Contemporary Islamic Studies, 2018)
Development of waqf land is capable of generating good development revenue for mutual benefits. However, there are many problems hindering the implementation of a good administration and management. Among the common problems, arise in the land administration are the registration of the Waqf land. Therefore the requirement of registration of waqf land is viewed as an important element in order to avoid any ambiguity or unexpected in the future. The purpose of this study is to explore the problem faced by the institution of Waqf in order to handle the problem of unregistered of waqf land in the state of Selangor. This paper also aims to expose the implications of the failure to register a Waqf land that raises various problems from a legal perspective. Among the effects to be dealt with the invasion of waqf land, adverse possession, acceptance of compensation under the Land Acquisition Act 1960, tax arrears, leasehold contracts and waqf land rental as well as claims and sales by heirs of the al-waqif. In other that, in this study are using qualitative method and select purposive sampling with semi-structured interview has been conducted to the representative of the waqf institution which is Perbadanan Waqf Selangor (PWS). Lastly, this paper is expected to open the eyes of all parties involved in dealing with Waqf land relating to the importance of compliance with the registration requirements of the title as provided under KTN.